Back to Course
JSS3: MATHEMATICS  1ST TERM
0% Complete
0/0 Steps

Binary Number System I  Week 15 Topics1 Quiz

Binary Number System II  Week 26 Topics1 Quiz

Word Problems I  Week 34 Topics1 Quiz

Word Problems with Fractions II  Week 41 Topic1 Quiz

Factorisation I  Week 54 Topics1 Quiz

Factorisation II  Week 63 Topics1 Quiz

Factorisation III  Week 73 Topics1 Quiz

Substitution & Change of Subject of Formulae  Week 82 Topics1 Quiz

Simple Equations Involving Fractions  Week 93 Topics1 Quiz

Word Problems  Week 101 Topic1 Quiz
Participants 9899

Do you like this content?
Follow us
Lesson 7, Topic 2
In Progress
Difference of Two Squares
Lesson Progress
0% Complete
(x + a) (x – a) = x(x – a ) + a (x – a )
= x^{2} – ax + ax – a^{2 }
= x ^{2} – a^{2}
The above result is called the difference of two squares
We can state the above relating as follows.
The difference of two squares is equal to the product of their sum and their difference.
Factorize the following expression completely
i. p^{2} â€“ q^{2} = (p â€“ q) (p + q)
p (p + q) â€“ q (p + q)
p^{2} + pq â€“ pq â€“ q^{2}
p^{2} â€“ q^{2}
ii. (x^{2} – a^{2}) = (x^{2}) â€“ (a^{2})
= (x â€“ a) (x + a)
x (x + a) â€“ a (x + a)
x^{2} + ax â€“ ax â€“ a^{2}
x^{2} â€“ a^{2}
iii. 2^{2} â€“ t^{2} = (2)^{2} â€“ (t)^{2}
= (2 â€“ t) (2 + t)
iv. 16s^{2} â€“ 4t^{2} = (4s)^{2} â€“ (2t)^{2}
= (4s â€“ 2t) (4s + 2t)
v. 121 â€“ 9y^{2} = (11)^{2} – (3y)^{2}
= (11 â€“ 3y) (11 + 3y)
Responses